EDUPRENEURSHIP BERBASIS TEKNOLOGI DIGITAL DITINJAU DARI EVALUASI PROGRAM CIPP - Istiningsih Istiningsih; Nur Rohman (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to see the achievement of edupreneurship as the goal of the  PGMI UIN Sunan Kalijaga Yogyakarta Study Program institution which is implemented through a series of learning activities.  To see this achievement, the authors used a qualitative descriptive research method with the CIPP program evaluation model as a tool to evaluate the eduprenenurship program.  The results of the research obtained are: first, contex evaluation  includes a description of edupreneurship, the position of edupreneurship in the curriculum, and edupreneurship as the goal of the PGMI study program.   Second, the input evaluation  includes Human Resources (HR) in this case lecturers, the Business Development Center (PPB) as a supporting institution, and all PGMI study program students who are targeted.   The three evaluations of prosess start from the planning stage which includes the preparation of curriculum programs, rps and syllabus; the implementation stage in the form of program implementation activities as outlined in digital technology-based learning activities; as well as the evaluation stage which includes student assessment activities both in terms of theory and practice.  Fourth, product  evaluation  in the form of student scores based on theoretical exams and entrepreneurial products in the form of private tutoring, making digital-based learning media, and selling books run by students of the PGMI UIN Sunan Kalijaga Yogyakarta Study Program.